Research on an electromagnetic device and pressuring force for measuring the depth of borehole while drilling the bone. (19th June 2020) - Wang, Xuan; You, Fangyi; Hong, Jian; Zhou, Wang
A device for measuring the depth of the borehole base on the magnetic grid during orthopedic surgery is proposed in this article. It consists of a magnetic grid, winding sleeve, two Hall sensors, and control circuitry. The magnetic grid comprises permanent magnets and coil windings. The device fixes on the electric hand drill and works during the surgical operation. An axial pressure keeps the shaft end of the magnetic grid in contact with the surface of the bone or the plate steadily during the electric handheld drilling of the bone. The pressure is an electromagnetic force generated by the interaction between the permanent magnets and the coil windings. The force should be large enough to support the weight of the magnetic grid and a low fluctuation is maintained. The larger the device, the higher the electromagnetic force will be generated. The electromagnetic force is simulated and obtained with the software of Maxwell. The factors that influence the force were the permanent magnet, and the others are the length of permanent magnet and the turns on the coil. The results of orthogonal simulation show that the primary factor is the diameter of the permanent magnet. The optimized parameters include the following: the diameter of the magnet is 7 mm, length of each permanent magnet is 5 mm, and the turns on the coil are 80. Then the pressure force range is approximately 0.485–0.716 N, and the variance of the force is 0.137.